Emerging ferromagnetic materials for electrical spin injection: towards semiconductor spintronics - Yufang Xie; Su-Yun Zhang; Yin Yin; Naihang Zheng; Anwar Ali; Muhammad Younis; Shuangchen Ruan; Yu-Jia Zeng (npj Spintronics)
Abstract Spintronics is a promising field beyond complementary metal-oxide semiconductors technology. It presents a unique approach to diminishing the energy consumption of memory and logic devices by utilizing spin. The proposed influential memory and logic device is the spin transistor. However, limited spin injection efficiency from the metallic ferromagnetic electrode into the semiconductor layer has been a major obstacle for the advances of spin transistors. Three key properties are critical for magnetic materials in future spintronic devices to improve the spin injection efficiency, namely high spin polarization, robust room-temperature ferromagnetism, and comparable resistance with the semiconductor. Considering these factors, we will explore four major categories of ferromagnetic materials: Heusler alloys, dilute magnetic semiconductors, Si- or Ge-based intermetallic compounds, and two-dimensional ferromagnets. We present a comprehensive overview of the significant milestones for each type of material in terms of their property improvements, functionality achievements, and fundamental applications for spintronics. Finally, we will briefly address the challenges which need to be tackled for practical application in memory and logic devices.